خصوصية الإثبات في الدعوى الإدارية دراسة تحليلية – مقارنة - دانا, عبد الكريم سعيد; بلند, أحمد رسول (University of Eloued جامعة الوادي, 2020)
نظراً لخصوصية الدعوى الإدارية بسبب وجود الإدارة فيها كمدعى عليه، والمتمتعة بإمتيازات وسلطات غير مئلوفة في الدعوي المدنية، والتي تخل بالتوازن ما بين أطرافها، أصبح للإثبات أمام القضاء الإداري أهمية كبيرة، وبالتالي أصبح له قواعد وإجراءات خاصة، وإن لم يكن مقننة، تجعل من سلطات القاضي الإداري وتوزيع عبء إثبات أمامه مختلفة عما هو عليه في الدعوى المدنية، على الرغم من إحالة غالبية قوانين مجلس الدولة المقارنة الى قواعد قانون الإثبات والمرافعات المدنية، سيركز هذا البحث على بيان هذه الخصوصية من خلال مبحثين. Considering distinctiveness of administrative lawsuit due to the presence of the administration as a defendant, which entitles privileges and powers not familiar in civil lawsuits, and which disrupts the balance between its parties, the issues of proof before the administrative court has become of great importance, and thus it has special rules and procedures, although not codified, that makes the power of the administrative judge and the distribution of the burden of proof before him differs from civil lawsuit. Despite the referral of most of the comparative State Council laws to the Laws of Evidence and Civil Procedures, this research will focus on this exclusiveness feature through two chapters.
مجلد4، عدد3
Keywords: خصوصية- الإثبات – الدعوى- الإدارية; Distinctiveness Features - Proof in Administrative Lawsuit